PENDIDIKAN MULTIKULTURAL DAN NASIONALISME INDONESIA - Tukiran Tukiran (Sosio-Didaktika: Social Science Education Journal, 2014)
AbstractIn this article the author promotes a conception of multicultural education and its role for the formation of Indonesian nationalism. Various references indicate that today there are some problems, mainly related to the  development of  narrow  ethnic  consciousness  in  some  areas  of the  country.  Not  infrequently inter- ethnic relations have led to excessive sentiment in some areas so disrupt national unity built since this nation stands. This phenomenon encourages awareness to make an effort to develop nationalism among the people of In donesia. In this case, multicultural education can be adopted for the solution of the problem. Multicultural  education appropriate to build Indonesian nationalism in the face of global challenges, because it has a core value in the local and global perspectives, namely: (a) piety towards God Almighty, (b) the responsibility of the unitary state, (c) an award, recognition, and acceptance of cultural diversity, (d) uphold the rule of law, and (e)appreciation of human dignity and human rights are universal. The goal of multicultural education is very importa nt for the integration of the nation because it is in line with Indonesian nationalism development efforts  to address the challenges of time.